The Effect of HIV/AIDS Education Prevention Using Web-Based She Smart on Knowledge, Attitudes, and Practice in Adolescent Girls. (2022) - Muslimin, Komala Dewi; Baso, Yusring Sanusi; Hidayanty, Healthy; Syarif, Syafruddin; Aminuddin, Aminuddin; Bahar, Burhanuddin
No abstract available